Proceedings of the 22nd International Conference on Industrial Engineering and Engineering Management 2015 Core Theory and Applications of Industrial Engineering (Volume 1) - Qi, Ershi; Shen, Jiang; Dou, Runliang; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2016)
Being the premier forum for the presentation of new advances and research results in the fields of Industrial Engineering, IEEM 2015 aims to provide a high-level international forum for experts, scholars and entrepreneurs at home and abroad to present the recent advances, new techniques and applications face and face, to promote discussion and interaction among academics, researchers and professionals to promote the developments and applications of the related theories and technologies in universities and enterprises, and to establish business or research relations to find global partners for future collaboration in the field of Industrial Engineering. All the goals of the international conference are to fulfill the mission of the series conference which is to review, exchange, summarize and promote the latest achievements in the field of industrial engineering and engineering management over the past year, and to propose prospects and vision for the further development. This volume is the first of the two proceedings volumes from this conference.
Modeling and Optimization of Functional Response Based on Kriging Model -- Evaluation of Auto Parts Industry Cluster in Jiangxi Province -- ReliefF Based Forward Selection Algorithm to Identify CTQs for Complex Products -- The Research on Cost Management of steel-plastic composite pipe enterprise based on Activity-Based Costing -- The Operations and Strategy for Container Yard Operators in Xiamen Port -- The Way of the Ease Traffic Congestion in Commercial Center of Beijing -The Analysis and Research of Level Analyses And Fuzzy Evaluation in Sanlitun Street -- Hierarchical Planning and Control Method for Multiple Product Development Projects -- A Virtual Resequencing Problem in Automobile Paint Shops -- Multi-objective Simulation Optimization Using Stochastic Kriging -- Age-Related Differences In The Acceptance Process Of Mobile Phones: A Closer Look At Social Influences -- Performance of the Zone Control Chart for Detecting Prespecified Quadratic Changes in Linear Profiles.
Keywords: Construction industry -- Management; Industrial Management; Construction Management; Industrial Management